Bio-Functional Natural Products in Edible Resources for Human Health and Beauty - Morikawa, Toshio (2022)
Natural products remain important repositories of promising therapeutic candidates due to their rich chemical and biological diversity. The Special Issue on "Bio-functional Natural Products in Edible Resources for Human Health and Beauty" is intended to offer biological active natural products from edible resources as candidates and/or leads for pharmaceuticals, dietary supplements, functional foods, cosmetics, and food additives, etc. The research fields of this Special Issue include natural products chemistry, phytochemistry, pharmacognosy, food chemistry, bioorganic chemistry, chemical biology, molecular biology, molecular pharmacology, and other related research fields of bioactive natural products obtained from the edible resources. This eBook contains 12 Reviews and Articles focusing on these research areas. I hope that this eBook will be of benefit to outstanding professionals in these research areas.